2004
DOI: 10.4081/monaldi.2004.693
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary haemodynamics in patients with OSAS or an overlap syndrome

Abstract: Background. Alveolar hypoxia is the most important mechanism leading to pulmonary arterial vasoconstriction, remodelling and pulmonary hypertension. Patients with Obstructive Sleep Apnoea Syndrome (OSAS) experience multiple short periods of alveolar hypoxia during apnoeic episodes. However, the question as to whether these hypoxic episodes are responsible for the development of permanent pulmonary hypertension is still debatable. We aimed to investigate the relationship between the episodes of nocturnal desatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 20 publications
(20 reference statements)
2
36
0
5
Order By: Relevance
“…131 In one case series, pulmonary hypertension was observed in 86% of those with COPD comorbid with OSA (n = 17) compared to only 16% of patients with OSA but no COPD (n = 67). 132 The incidence of right heart failure in comorbid COPD and OSA was 12% in another case series, and was associated with lower mean nocturnal oxygen saturation, lower awake PaO 2 , and higher PaCO 2 .…”
Section: Impactmentioning
confidence: 84%
“…131 In one case series, pulmonary hypertension was observed in 86% of those with COPD comorbid with OSA (n = 17) compared to only 16% of patients with OSA but no COPD (n = 67). 132 The incidence of right heart failure in comorbid COPD and OSA was 12% in another case series, and was associated with lower mean nocturnal oxygen saturation, lower awake PaO 2 , and higher PaCO 2 .…”
Section: Impactmentioning
confidence: 84%
“…[66][67][68][69][70][71][72][73] For example, Hawrylkiewicz and colleagues observed that 16% of those with OSA had pulmonary hypertension, compared with 86% of those with overlap syndrome. 74 Several pulmonary parameters have been shown to increase mortality in patients with OSA. Both the diagnosis of concomitant COPD and markers of COPD, such as a reduced FEV 1 or smoking history, have been shown to be markers for increased mortality in OSA patients.…”
Section: Copd and Osa: "The" Overlap Syndromementioning
confidence: 99%
“…Increased sympathetic surges associated with IH as compared to the continuous hypoxia (55) may reflect the oxidative stress produced by rebound hyperemia. Oxidative insult promotes the release of proinflammatory mediators, such as cyclo-oxygenase-2, tumor necrosis factor-alpha, and interleukins (56-58) leading to systemic inflammation, endothelial dysfunction and culminating in vascular non compliance (59). The dysfunctional endothelium has been observed in SDB patients without any overt vascular disease and is a precursor to atherogenesis, thrombogenesis, and reduced vascular lumen (54,55,60).…”
Section: Oxidative Stress and Systemic Inflammationmentioning
confidence: 99%